An Investigation Of Consumer Misdemeanour: Consumer Evaluations Of Brand Imitations - Lynn, Lim (2008)
The intention of this paper has been to investigate and understand consumer evaluations on the demand toward brand imitations in the Malaysian context. The discussion is delimited to consumer products of imitation.